The determination of value of soybean and lemongrass plants factors using small plots and USLE methods on Andepts soil in Kwala Bekala Estate USU - Dwi Ayu Febrina; Sumono Sumono; Lukman Adlin Harahap (Universitas Sumatera Utara, 2013)
One way to overcome erosion is using vegetative methods, where its influence can be manifested by the C factor. The best C factors used in determining the amount of erosion is the value of C in the local area. This study was aimed to determine the value of soya bean and lemongrass crop factor on the Andepts soil during March to July 2013 using the method of small plots and USLE. Parameters used in determining the C factor were the amount of erosion, the allowable erosion rate, and the erosion hazard level. The results showed that the amount of erosion on land without a crop was 0,46 ton (ha.year)-1, on lemongrass land was 0,39 ton (ha.year)-1, on soybeans land was 0,30 ton (ha.year)-1. The amount of allowable erosion rate was 32 ton (ha.year)-1. While erosion hazard rate on land without a crop was 0,014; on lemongras land was 0,012 and on soybeans land was 0,009 which include in low category. The value of soybeans crop factor using rainfall research data for 4 months and 10 years data was 0,655 and 0,666 respectively. The value of lemongrass crop factor using rainfall research data for 4 months and 10 years data was 0,851 and 0,866 respectively. Key words : andepts, C factor, erosion,, Kwala Bekala USU